Analisis Faktor-Faktor Mempengaruhi Kejadian Hipertensi di Poliklinik penyakit Dalam - Marlena, Marlena (Universitas Fort De Kock Bukittinggi, 2020)
Background: Based on the Rikesdas in 2018, the prevalence of hypertension cases in West Sumatra Province for the Mentawai Islands Regency was recorded at 17.7%. The research objective: To determine the factors those influence the incidence of hypertension in patients visiting the internal disease polyclinic of the Mentawai Islands Regional General Hospital in 2020. Method: Mixed method with a Sequential Explanatory design. Samples were 80 patients with hypertension who happened to visit the internal disease polyclinic of the Mentawai Islands District General Hospital while the observation was taking place, totaling 80 respondents; the sampling technique was Accidental Sampling. Chi-square data analysis with a value of α = 0.05. 14 informants were selected purposively. Results: The results of the Chi-Square statistical test showed no variables that were significantly related to the incidence of hypertension with p value> 0.05, these variables were gender (p = 0.716), family history (p = 0.443), education level. (p = 0.213), level of knowledge (p = 0.185), age (p = 0.734), ethnicity (p = 0.213), physical activity (p = 1,000). Conclusion: in this study there are no factors that affect the incidence of hypertension in the internal disease polyclinic of the Mentawai Islands District Public Hospital, like doing a nutrition consultation.Keywords: Hypertension, Determinant, internal disease